A Study of University Students’ Communication Behavior in Social Media from Theory of Uses and Gratification - Alimuddin, Nurwahida; Latepo, Ibrahim (Journal of Humanities and Social Sciences Studies, 2021)
University students have intensively used social media in their daily life. The students use social media for social, education, and interaction purposes. Some studies found that students also use social media for psychological relief benefits such as building happiness through making friends and finding entertainment. However, limited studies have been conducted to find out variables that affect psychological needs in social media use. This study, therefore, aims to find out variables that affect university students' psychological needs in social media use. This study used a quantitative method with a survey approach. Samples were eighty students who were purposively recruited from four faculties. This study shows that information search, social interaction, entertainment, narcissism, and attention seekers behavior have significantly influenced the students' motivation to fulfill psychological needs in social media use. Personal identity-building did not affect the students’ use of social media in fulfilling their psychological needs. The students might be focused on social identity rather than personal identity building. We concluded that social media had become a new source for university students to find psychological relief and well-being.